2022
DOI: 10.1038/s41598-022-15978-x
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed reconstruction for bile duct injury a multicenter retrospective analysis of a hepatopancreaticobiliary group

Abstract: Common bile duct injury is a severe complication. It is related to increased rates of morbidity and mortality. Early recognition and on-time diagnosis plus multidisciplinary management of this disease led by a hepatobiliary surgeon show fewer complications rate and best postoperative outcomes. However, no guidelines exist about the proper time of reconstruction. This study aims to describe the experience of a specialized Hepato-Pancreatic-Biliary (HPB) group and to analyze the outcomes regarding the time of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…3). A multicenter retrospective study also reported [17] a statistically signi cant correlation between the presence of biliary tract tumors and the severity of bile duct injury (P = 0.02). The correlation of complicated bile duct injuries is eventually a clear diagnosis of Strasberg-Bismuth E3-5 biliary injury risk increased 41.7 times.…”
Section: Discussionmentioning
confidence: 91%
“…3). A multicenter retrospective study also reported [17] a statistically signi cant correlation between the presence of biliary tract tumors and the severity of bile duct injury (P = 0.02). The correlation of complicated bile duct injuries is eventually a clear diagnosis of Strasberg-Bismuth E3-5 biliary injury risk increased 41.7 times.…”
Section: Discussionmentioning
confidence: 91%